2019
DOI: 10.1007/s10620-019-05722-3
|View full text |Cite
|
Sign up to set email alerts
|

A Cholecystokinin Receptor Antagonist Halts Nonalcoholic Steatohepatitis and Prevents Hepatocellular Carcinoma

Abstract: Background and Aims Nonalcoholic steatohepatitis (NASH) is a common inflammatory liver condition that may lead to cirrhosis and hepatocellular carcinoma (HCC). Risk factors for NASH include a saturated fat diet, altered lipid metabolism, and genetic and epigenetic factors, including microRNAs. Serum levels of cholecystokinin (CCK) are elevated in mice and humans that consume a high-saturated fat diet. CCK receptors (CCK-Rs) have been reported on fibroblasts which when activated can induce fibrosis; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…CCK receptors have been characterized on stellate cells of the pancreas [59] and on fibroblasts [60] and stimulation of these receptors results in collagen deposition and fibrosis. We have previously shown that proglumide therapy could decrease fibrosis by preventing stellate cell activation in the mouse liver [21] and in the pancreas microenvironment [61]; therefore, we assume that the anti-fibrotic effect seen in the livers of the CDE-fed mice treated with proglumide in this investigation was related to the blockade of the CCK receptor on mouse stellate cells in the liver. The reduction in hepatic inflammation observed in the CDE/Prog-treated mice of this study may be due to proglumide's action on reducing inflammatory cytokines and chemokines as previously described [27].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…CCK receptors have been characterized on stellate cells of the pancreas [59] and on fibroblasts [60] and stimulation of these receptors results in collagen deposition and fibrosis. We have previously shown that proglumide therapy could decrease fibrosis by preventing stellate cell activation in the mouse liver [21] and in the pancreas microenvironment [61]; therefore, we assume that the anti-fibrotic effect seen in the livers of the CDE-fed mice treated with proglumide in this investigation was related to the blockade of the CCK receptor on mouse stellate cells in the liver. The reduction in hepatic inflammation observed in the CDE/Prog-treated mice of this study may be due to proglumide's action on reducing inflammatory cytokines and chemokines as previously described [27].…”
Section: Discussionmentioning
confidence: 84%
“…In rodents, proglumide increases bile flow [20] and decreases bile acid concentration. We previously showed that proglumide therapy prevented and reversed biochemical and histologic NASH in mice fed a choline deficient ethionine (CDE) diet [21]. In this model, we found that proglumide significantly reduced serum bilirubin levels, suggesting that proglumide was stimulating bile flow and reversing hepatocyte injury.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This prospective open-labeled clinical trial undertaken at Georgetown University was an investigator-initiated translational research study based upon a study in mice that showed reversal of hepatic fibrosis and prevention of hepatocellular carcinoma [ 19 ]. The protocol and sample size were approved by the Food and Drug Administration (FDA) and the Georgetown University Institutional Review Board (IRB), and the trial was registered on (accessed on 20 February 2022) (NCT04814602).…”
Section: Methodsmentioning
confidence: 99%
“…The cholecystokinin-B receptor (CCK-BR) is not found in normal liver tissue (mouse or human) but becomes overexpressed in NASH and HCC [ 18 ]. In fact, in [ 19 ] 35% of the mice on a NASH-inducing diet developed dysplastic nodules or HCC after 18 weeks, while none of the mice treated with a CCK-BR antagonist, proglumide, developed HCC. Further examination of the mouse NASH livers in this study showed that treatment with the CCK receptor antagonist, proglumide, rendered the liver microenvironment less carcinogenic by decreasing fibrosis, inflammatory chemokines, and cytokines and reducing M2-polarized macrophages [ 18 ].…”
Section: Introductionmentioning
confidence: 99%